Pengaruh kompensasi finansial dan disiplin kerja terhadap kinerja karyawan - Fikri Mu'tashim; Zainal Ilmi; Dirga Lestari AS (Jurnal Ilmu Manajemen Mulawarman (JIMM), 2018)
This study aims to find out whether there influence of financial compensation and discipline of work to the personal work performance PT. Buluh Perindu Kota Samarinda. The population is 43 people, which is all becoming respondent on this research. This research use primary data who obtained with the spread of questionnaries to employees who working on PT. Buluh Perindu Kota Samarinda. Data analysis technique used in this research multiple linear regression, which is operated throught the program SPSS 20. The result of this study indicate that financial compensation has influence to the employee performances, work discipline has influence to the employee performances.Keyword: Financial Compensation, Work Discipline and Employee Performance